Menggagas Sistem Ekonomi Alternatif (Upaya Mencari Kedudukan Ekonomi Islam) - Mashur Malaka (Al-'Adl, 2008)
What Paul A. Samuelson discloses in The Family of Economic which he calls The Main Stream of Economic, if we look further we will soon encounter a vacuum of economic thought from the first year of the AD until the discovery of ST. Tomas Aquinas in 1270 AD at that time interval according to "The family tree of economic" is filled with the normative scholastic thought.It is an unavoidable fact that Muslims have lost their thinking power for hundreds of years. Imitation of the western mind without any cross check the source of thought makes Muslims blinded by innovations that are born in various fields. The view of Muslims seems to be closed by the concepts laid down, so the effort to compromise them with Islamic concepts seems unthinkable. Muslim dependence on the concept offered makes it inferior to the Islamic ability to find solutions to the problem of life in all things. Yet Allah promises perfection of Islam as Religion as well as life guidance.Historical books of economic thought do not exist, or if any such as Schumpeter merely touches on a few lines of explanation of the old contributions of Islam. A very ironic thing, given Adam Smith, who is famous as the father of Economics mentioned in "The Wealth Of Nation" that the advanced economy is an Arab economy led by Muhammad and His Immediate Successor.This irrationality recurred when Samuelson explained the diagram of the origin of economics. He listed the Bible as the origin of the science, none of the economists objected when the Islamic scientists reappointed Islamic economics and made the Qur'an and Hadith a source of reference for many economists who rejected it including Muslim economists.To quote Adiwarman Karim's statement, if we would honestly admit that economics is the heritage of human civilization, it is like a tiered building of the level that every people has contributed to thinking in their own time. Fortunately, the storm of the economic crisis makes our minds re-enlightened with a reality that the Islamic economic system that is endorsed by Islamic financial institutions is more able to survive than the capitalist and socialist economic system.